A multiscale-multiphysics integrated model to investigate the coupling effects of non-uniform illumination on concentrated photovoltaic system with nanostructured front surface. (1st January 2020) - He, Ya-Ling; Zhou, Yi-Peng; Hu, Yi-huang; Hung, Tzu-Chen
Highlights: A multiscale-multiphysics integrated model. Multiscale-multiphysics effects of non-uniform illumination. Nanostructures with lower reflectance result in stronger multiscale-multiphysics effects. Coupling effects of the distribution of the cooling system. Theoretical basis for the design of nanostructures and cool system. Abstract: Nanostructured front surface and concentrator can improve the photovoltaic performance by absorbing and concentrating more solar light. However, they lead to the non-uniform distribution of the absorbed solar radiation ( I a ), which has a great influence on the concentrated photovoltaic (CPV) system. In CPV system with nanostructured front surface, there are the complicated multiscale-multiphysics processes, which include geometrical optics (concentrator), near-field optics (nanostructured front surface), photoelectric conversion (photovoltaics), and heat transfer (photovoltaic module). Hence, a multiscale-multiphysics integrated mathematical model is developed and applied in the physical model of a CPV system, which employs a linear Fresnel lens and a photovoltaics with the moth-eye nanostructured front surface. Six kinds of surface structures with different anti-reflection characteristics are chosen in this study. Investigation found that, with the decrease of the average reflectance of the nanostructure, the multiscale-multiphysics effects of the non-uniform I a on the photovoltaic characteristics are enhanced. Moreover, the higher temperature difference caused by the nanostructure with lower reflectance is one of the most important reasons for the difference between photovoltaic characteristics for the non-uniform I a and uniform I a . Therefore, the nanostructures with lower reflectance are not definitely good for CPV system. In order to reduce the effects of photovoltaic temperature with non-uniform distribution, it has been studied that the variation of the CPV performance with the bottom convective heat transfer coefficient ( h b ). It is found that when the reflectance of nanostructure is too low, the multiscale-multiphysics effect of non-uniformity I a is enhanced as the uniform h b increases, the "turning" point of temperature appears, which is caused by the non-uniform distribution of temperature. Finally, a normal distribution of the h b is applied for reducing temperature difference. It is found that, with the increase of the maximum in normal distribution of h b, the temperature difference does decrease, but the CPV performance decrease due to higher average temperature of CPV. Therefore, the design of cooling system for CPV system should focus on the cooling capacity rather than the distribution.